ANALISIS KINERJA PEGAWAI PADA BIDANG PELAYANAN DAN INFORMASI DI BADAN PENANAMAN MODAL DAN PELAYANAN PERIZINAN TERPADU KABUPATEN SIAK - Riki Kurniawan; Nurmasari Nurmasari (UIR Press, 2018)
The research was conducted at the Field Services and Information on Board of Investment and Integrated Licensing Services Siak.The purpose of this study to determine and explain the performance of employees at the Field Services and Information on Board of Investment and Integrated Licensing Services Siak.Sampling method in this study, for employees is conducted by using census method because it is considered more relevant, the number of population and the sample relative bit and be in a place with this research.Data collection techniques used consist of primary data collected by using a list of interviews and secondary data were collected by using observation and documentation.While data analysis technique used is descriptive method.Where the descriptive method to describe the full reality of the performance of employees in Field Services and Information on Investment Board and Integrated Licensing Services Siak.Once the data is collected, then subsequently grouped for descriptive analysis were presented in accordance with the withdrawal of a conclusion.As for the results of research conducted by researchers with the title